Enhancing Socio-Economic Well-being: The Role of Village Funds in Nagan Raya Regency - Hajad, Vellayati; Putri, Dinda Zulmainia; Ikhsan; Setiawan, Deni; Herizal (Ilomata International Journal of Social Science, 2024)
This study examines the role of effective communication in enhancing the management of Village Funds for community empowerment in Nagan Raya Regency. Utilizing a qualitative approach, including interviews, focus group discussions, and document analysis, data was collected from local government officials, community leaders, and residents involved in Village Fund management. Thematic coding was employed for data analysis to identify critical patterns and themes related to communication processes and Village Fund management effectiveness. The findings reveal that effective communication between local government and communities is crucial for the success of Village Fund management. Open and inclusive communication facilitates active community participation in decision-making, leading to the identification of community needs and priorities. Moreover, transparent and accountable communication practices foster trust and collaboration between stakeholders, contributing to the sustainable development of Nagan Raya Regency. In conclusion, this study emphasizes the significance of effective communication in optimizing Village Fund utilization for community empowerment. Maintaining open, inclusive, and responsive communication channels ensures that Village Funds address community needs and promote sustainable development. The study underscores the importance of ongoing efforts to strengthen communication mechanisms and foster collaboration between local government and communities to enhance the impact of Village Fund initiatives on community well-being in Nagan Raya Regency.